(untitled) (Journal of Hama University, 2025)
Studying the optimal operation of water distribution networks is one of the important issues for plans to manage the operation of these networks. In recent years, methods for arriving at optimal solutions have gained great importance in this field because they have proven to be of great effectiveness and high accuracy. In this research, simple genetic algorithms technology was used to study the optimal operation of the drinking water network in the Al-Waer neighborhood in Homs Governorate, so that the hydraulic requirements for flow are met, and with the lowest possible economic investment cost for operation, with a proposal to establish a balance tank and study the possibility of feeding the network from the tank and pumps together, as The WaterCAD program was used for hydraulic simulation, and the results showed the efficiency of the simple genetic algorithm in managing the operation of the network well, as it was found that the pumped volume of water (1179.8 m3) is sufficient to supply the network in an acceptable manner, with the possibility of stopping each pump from working for 6 hours, and feeding the network from the pumps and the tank. Together, the pumping investment costs amount to (102,798 SYP) per day.